Combination of Natural Compounds With Novel Non-thermal Technologies for Poultry Products: A Review - Barroug, Soukaina; Chaple, Sonal; Bourke, Paula (Frontiers in Nutrition, 2021)
Ensuring safe, fresh, and healthy food across the shelf life of a commodity is an ongoing challenge, with the driver to minimize chemical additives and their residues in the food processing chain. High-value fresh protein products such as poultry meat are very susceptible to spoilage due to oxidation and bacterial contamination. The combination of non-thermal processing interventions with nature-based alternatives is emerging as a useful tool for potential adoption for safe poultry meat products. Natural compounds are produced by living organisms that are extracted from nature and can be used as antioxidant, antimicrobial, and bioactive agents and are often employed for other existing purposes in food systems. Non-thermal technology interventions such as high-pressure processing, pulsed electric field, ultrasound, irradiation, and cold plasma technology are gaining increasing importance due to the advantages of retaining low temperatures, nutrition profiles, and short treatment times. The non-thermal unit process can act as an initial obstacle promoting the reduction of microflora, while natural compounds can provide an active obstacle either in addition to processing or during storage time to maintain quality and inhibit and control growth of residual contaminants. This review presents the application of natural compounds along with emerging non-thermal technologies to address risks in fresh poultry meat.